(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This article is dedicated to the study of the socio-psychological determinants of loneliness among students. It explores social and psychological factors, including interpersonal relationships among students, academic difficulties, family circumstances, and self-perception. The article also discusses how feelings of loneliness among students affect their psychological state, self-esteem, and overall well-being.